The Impact of Immersive Learning Assisted by Virtual Reality and Automated Writing Evaluation on Writing Skills and Higher-Order Thinking Skills - Lisa Novia; Ade Hikmat; Imam Safi’i (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Most high school students still struggle with writing observational texts, particularly when it comes to describing objects in detail, critically, and creatively. This study aims to examine the impact of immersive learning supported by augmented reality (AR) and automated writing evaluation (AWE) on students’ writing skills and higher-order thinking skills. This study used a quasi-experimental method involving 250 high school students divided into an experimental group and a control group. The experimental group received AR- and AWE-assisted immersive learning, while the control group received conventional instruction. Data collection was conducted using a writing skills assessment rubric, a higher-order thinking skills questionnaire, and feedback coding. Data were analyzed using ANCOVA, the Chi-square test, and mediation analysis.The results of the study indicate that AR- and AWE-assisted immersive learning has a significant impact on improving writing skills and higher-order thinking skills compared to conventional learning. Improvements in writing skills were observed in task achievement, coherence and cohesion, vocabulary use, as well as grammatical variety and accuracy. Additionally, the use of AR and AWE fosters reflection, critical thinking, creativity, metacognition, and problem-solving skills among students. This study concludes that the integration of technology in writing instruction can optimize writing competencies while simultaneously enhancing higher-order thinking skills and the quality of the learning process.